2015
DOI: 10.2147/ijn.s89476
|View full text |Cite
|
Sign up to set email alerts
|

Hyaluronic acid-tagged silica nanoparticles in colon cancer therapy: therapeutic efficacy evaluation

Abstract: Colon cancer is one of the leading causes of cancer-related death worldwide, and the therapeutic application of 5-fluorouracil (5-FU) is limited due to its nonspecificity, low bioavailability, and overdose. The present study is an attempt to improve the chemotherapeutic efficacy of 5-FU in colon cancers. Therefore, we have prepared 5-FU-loaded hyaluronic acid (HA)-conjugated silica nanoparticles (SiNPs) to target to colon cancer cells. In this study, we have showed the specific binding and intracellular accumu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…HA is reported to possess strong affinity toward the CD44 overexpressing cancer cells [ 38 ]. HA is nonantigenic and biocompatible and shows high affinity toward the receptors [ 39 ]. In addition, CD44 receptors are overexpressed in different human cancer cells and their density increases with the stages of cancers [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…HA is reported to possess strong affinity toward the CD44 overexpressing cancer cells [ 38 ]. HA is nonantigenic and biocompatible and shows high affinity toward the receptors [ 39 ]. In addition, CD44 receptors are overexpressed in different human cancer cells and their density increases with the stages of cancers [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…The distinctive different release behaviors of MSN-NH2-FU and MSN-NH2-FU-FA indicated that drugs encapsulated in FA-conjugated nanoparticles could release 5-FU as a sustained type of formulation for a longer time. The delayed release of the drug from MSN-NH2-FU-FA indicates that it can act as an efficient drug carrier and could minimize the exposure of anticancer agents to normal tissues and enhance the accumulation in tumor tissues [ 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…Solid lipid nanoparticles Colorectal Enhanced anticancer activity [32] Chitosan nanoparticles Colorectal Better targeting efficiency and localized drug in cancer cells [33] PLGA nanoparticles Colorectal Maximum cell-lysis effect and better targeting efficiency [34,35] Citrus pectin nanoparticles coated with Eudragit S100 Colorectal Prolonged drug release and enhance selectivity [36] Silica nanoparticles conjugated to hyalurocin acid Colon Enhanced cellular uptake and improved cytotoxicity [37] Aminofunctionalized MSN Colorectal Improved cytotoxicity and pH-responsive controlled drug release system [38] Alginate-chitosan nanoparticles Ocular application Enhanced ocular absorption and pharmacokinetics [39] Galactosylated chitosan functionalized MSN Colon cancer Enhanced anti-cancer activity and targeting [16] Chitosan and PEG coated MSNs Breast and cervical cancer Enhanced anti-cancer activity with the loading of two anticancer drugs [19] MSN Melanoma Enhanced anti-cancer activity and skin permeation [30] Carboxymethyl chitosan-coated MSN Ocular application Enhance ocular absorption and pharmacokinetic [31] Combination of 5-FU and cisplatin with electroporation Ovarian Enhanced anti-cancer activity [40] Folic acid and PLGA conjugates Colorectal Enhanced anticancer activity [41] Folate-conjugated polymers Colon Enhanced anti-cancer activity and targeting [42] PLGA folate-conjugated peptide nanoparticles Melanoma Enhanced cytotoxicity and targeting [43] Bi-MIL-88B MOF nanoparticles coated with chitosan-folic acid conjugate Colon Enhanced anti-cancer activity and targeting [44] MSN nanoparticles coated with folic acid-modified lipid Breast cancer Enhanced cytotoxicity and targeting with the loading of two anticancer drugs [45] 2. Materials and Methods…”
Section: Cancer Advantages Referencementioning
confidence: 99%
“…As CD44 is overexpressed in many malignancies and HA has a strong attraction for it, target-selective drug administration using HA-conjugated drug delivery devices has been investigated [111]. For instance, earlier research [111,112] looked at the efficiency of mesoporous silica nanoparticles enhanced with HA in focusing on cancer cells that overexpress CD44. In order to target inflamed intestinal mucosa, Vafaei et al [113] created self-assembled HA nanoparticles for colonic delivery of budesonide.…”
Section: Hyaluronic Acidmentioning
confidence: 99%